2012
DOI: 10.3109/09540261.2012.655713
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in Austria: Mental health trialogue

Abstract: The active involvement of service users and relatives and friends is essential for the development of recovery-orientated mental health practice and research. However, accepting each other as equally entitled experts is still a challenge. In trialogue groups users, carers and friends and mental health workers meet regularly in an open forum that is located on 'neutral terrain' - outside any therapeutic, familial or institutional context - with the aim of discussing the experiences and consequences of mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
2
27
0
6
Order By: Relevance
“…Since then, well over 150 Trialogue Meeting groups have been established in Germany, Austria, Switzerland, Poland, Turkey, Trinidad, China, US, Toronto UK and Ireland [1415, 1718]. In addition to anecdotal reports from participants that engaging in Trialogue Meetings are positive and transformative experiences [141516, 1819], two small-scale evaluations [2021] and one large-scale national evaluation [22] have demonstrated that Trialogue participation can result in improved outcomes such as lower anxiety and enhanced communication skills. However, in spite of such promising findings, there is a dearth of research on the specific processes involved in participating in Trialogue Meetings in mental health contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, well over 150 Trialogue Meeting groups have been established in Germany, Austria, Switzerland, Poland, Turkey, Trinidad, China, US, Toronto UK and Ireland [1415, 1718]. In addition to anecdotal reports from participants that engaging in Trialogue Meetings are positive and transformative experiences [141516, 1819], two small-scale evaluations [2021] and one large-scale national evaluation [22] have demonstrated that Trialogue participation can result in improved outcomes such as lower anxiety and enhanced communication skills. However, in spite of such promising findings, there is a dearth of research on the specific processes involved in participating in Trialogue Meetings in mental health contexts.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in a largely con sistent consensus which has seen recovery explicitly adopted in national policy across England (2001), Ireland (2005 and Scotland (2006), other Anglo phone countries, including New Zealand (1998), the USA (2003), Australia (2003) and Canada (2009), and close engagement in Italy (Davidson 2010b) and Northern Europe (Amering 2009(Amering , 2012. There are some cultural differ ences, and initial explorations in some Asian (Ahmed 2012;Thara 2012) and African (Katontoka 2012; Parker 2012) countries have illustrated variations in non-Western concepts of recovery which emphasise the importance of spirituality and a collective, rather than an individual, identity for health (Slade 2012b).…”
Section: International Understanding and Policymentioning
confidence: 99%
“…First, the literature review helped to identify two initiatives that met the research criteria: Trialogues and Mental health forums [6, 32]. Only Trialogues turned out to be relevant to this project.…”
Section: Results—description Of the Practicementioning
confidence: 99%
“…Initiated in Germany (where they are known as Psychosis Seminars) and extended to other countries in Europe (Austria, Ireland, etc. ), Trialogues allow groups of 10–60 people to exchange ideas on various topics relating to care experience, recovery, crisis management, and so on [6, 35]. Similar to the CCIU, Trialogues, established in recent years, provide a forum for dialogue between users, carers and mental health workers, outside institutional walls and on an equal footing [6, 33, 34].…”
Section: Results—description Of the Practicementioning
confidence: 99%